Pengembangan Kompetensi Religius Bagi Guru Bimbingan dan Konseling serta Calon Konselor Pendidikan - Wahidin Wahidin (Kuras Institute, 2022)
Religious competence is defined as the ability of the counselor in helping the counselee to develop optimally and the presence of happiness in life by believing in the role of God in the counseling process. The purpose of this study is to describe the importance of religious competence for BK teachers and prospective education counselors. The research method used is descriptive qualitative with interview techniques. The interviews were conducted in a structured manner with the following stages: (1) preparation (determining topics, determining data sources/respondents, compiling interview guidelines), (2) implementation (online and offline), and (3) preparing reports on the results of the interviews. The participants of this study were representatives from BKPI lecturers from IAIN Salatiga, UIN Sultan Syarif Kasim, IAIN Curup, and IAIN Batusangkar, each tertiary institution was taken by one BKPI lecturer. Total respondents in this study were 10 lecturers. The results of the study indicate that religious competence is very much needed for BK teachers and prospective education counselors. Religious competence for prospective education counselors can be implemented into the BKPI curriculum by integrating Islamic courses combined with guidance and counseling courses.